Parotidectomy: Surgical technique - Sarroca, Carlos; Valls, Alberto; De Vecchi, Jorge; Oreggia, Fernando (Cirugía del Uruguay, 1986)
This Symposium has the surgical technique of conservativa parotidectomy and its complicati6ns as its only and exclusive topic. Flrst, an anatomic review is made of the parotid gland and the glandular lodge, pointing out that they are fundamentally relatad to the facial nerve. Further on, the surgical technique is discussed laying special emphasis on the approach to and the handing of lhe facial nerve and its branches. Lastly, an analysis is made of complications, including nervous complications and the Frei syndrome and local recidivation.